The Effect of Omnichannel Experience on Repurchase Intention through Customer Satisfaction - Josephine Luin; Ronny Samsul Bahri (Eduvest - Journal of Universal Studies, 2025)
This study investigates the effect of omnichannel experience on repurchase intention through customer satisfaction at UNIQLO Indonesia. The research addresses the limited integration of physical and digital channels in Indonesian fashion retail and the lack of empirical evidence on its influence on customer loyalty. It fills a gap by examining customer satisfaction as a mediator in omnichannel dynamics within emerging markets, using a unique integration of Stimulus-Organism-Response (SOR), Expectation Disconfirmation Theory (EDT), and Theory of Planned Behavior (TPB)—a framework rarely applied in Southeast Asia. Quantitative PLS-SEM methods tested a mediation model based on primary data from 213 active UNIQLO app users. Analysis included instrument validation, structural model evaluation, and indirect effect testing. Results show omnichannel experience positively affects customer satisfaction (β = 0.957, p < 0.05), which in turn positively affects repurchase intention (β = 0.428, p < 0.05). Additionally, customer satisfaction mediates the relationship between omnichannel experience and repurchase intention (β = 0.409, p < 0.05), explaining 42.7% of the conversion from experience to loyalty. Theoretically, this study is the first to empirically validate the SOR-EDT-TPB model in the Indonesian fashion retail omnichannel context. Managerially, it recommends UNIQLO and similar retailers to enhance seamless channel integration and real-time personalization, suggesting investment in RFID inventory transparency, AI-driven personalization, and loyalty programs rewarding omnichannel engagement over single-channel use. The study provides a valuable framework for optimizing omnichannel experiences to boost repurchase intention in emerging markets.